Paradoxes of the „classical” market economy as the backbone elements of capitalism and integration policy - Валесян, С. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
This article discusses the basic postulates of classical market economy, the central concept which is the principle of self-regulation and policy of non-interference of the state in the process of commodity exchange. We study the basic system paradoxes associated with the work of laissez-faire, which are the guarantees for the emergence of anti-capitalist movements. Also analyzed the relationship of the basic contradictions of self-regulation of the market and their projection on the political instability in the state and society.